The Effect of Store Atmosphere on Behavioral Intention at Retail Store with Customer Emotions as Intervening Variables - Ilham Rahmanto; Ririn Tri Ratnasari (Universitas Airlangga, 2023)
ABSTRACT Fast-growing shopping centers have a good impact on the economy in Indonesia. The large Gross Domestic Product (GDP) and opening up wide employment opportunities is a form of the shopping center's contribution. The increasing number of shopping centers makes competition between shopping centers, especially small shops or retail stores a threat that cannot be underestimated for shop owners. One of the important strategies that can be applied to a store by store owners is to design a store atmosphere. Therefore, the purpose of this study was to determine the effect of store atmosphere on behavioral intentions at Hakata & Co retail stores in Mataram city with customer emotion as an intervention variable. This study used a quantitative approach technique. The data collection technique was by distributing offline and online questionnaires to 60 respondents less than 15 years old to more than 35 years old and had come and or shopped at the Hakata & Co store. The analytical technique used in this research was AMOS SEM with AMOS-22 Software. The results of this study indicate that there is a significant positive relationship between each variable, namely store atmosphere, customer emotions, and behavioral intentions with the object of Hakata & Co. retail stores. Keywords: Store Atmosphere, Behavioral Intention, Customer Emotions, Retail Stores, Hakata & Co. ABSTRAK Pusat perbelanjaan yang semakin banyak dan berkembang membawa dampak baik bagi ekonomi di Indonesia. Produk Domsestik Bruto (PDB) yang besar dan membuka lapangan pekerjaan yang luas adalah bentuk dari kontribusi pusat perbelanjaan. Pusat perbelanjaan yang semakin banyak menjadikan persaingan antara pusat perbelanjaan khususnya toko-toko kecil atau juga bisa dibilang toko ritel menjadi ancaman tersendiri yang tidak bisa disepelekan bagi pemilik toko. Salah satu strategi yang penting dan bisa diterapkan pada sebuah toko oleh pemilik toko yaitu dengan merancang Store Atmosphere toko. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui pengaruh store atmoshere terhadap behavioral intention pada toko ritel Hakata & Co di kota Mataram dengan customer emotions sebagai variabel intervening. Penelitian ini menggunakan Teknik pendekatan kuantitatif. Adapun teknik pengumpulan data yaitu dengan menyebarkan kuesioner secara offline dan online kepada 60 responden berusia kurang dari 15 tahun sampai dengan lebih dari 35 tahun dan sudah pernah datang dan atau berbelanja ke toko Hakata & Co. Teknik analisis yang digunakan dalam penelitian ini adalah SEM AMOS dengan Software AMOS-22. Hasil penelitian ini menunjukkan bahwa adanya hubungan positif signifikan antara setiap variabel yaitu store atmosphere, customer emotions dan behavioral intention dengan objek toko ritel Hakata & Co. Kata Kunci: Store Atmosphere, Emotions, Behavioral Intention, Toko Ritel, Hakata & Co, Mataram